Physiological responses to four hours of low-level repetitive work - Garde, Anne Helene; Hansen, Åse Marie; Jensen, Bente R. (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The study investigated physiological responses to 4 hours of standardized low-level repetitive work. It was hypothesized that accumulative effects not observed after 1 hour could be found after 4 hours of repetitive work. ' ' METHODS ': 'Ten healthy women performed intermittent (5 seconds + 5 seconds) handgrip contractions at 10% of the maximal voluntary contraction combined with mental demands for concentration and attention. Muscle activity in the working forearm muscles, cardiovascular responses, and concentrations of biomarkers in biological fluids were recorded along with exerted force, performance, and ratings of perceived physical exertion (RPE), and perceived mental exertion. ' ' RESULTS ': 'The urinary epinephrine, norepinephrine, and cortisol concentrations were higher during the repetitive task than on a reference day, but only the norepinephrine concentrations increased progressively during the 4 hours. In accordance, the RPE recorded for the hand, forearm, and shoulder regions increased progressively. For the remaining physiological measures, no accumulative changes were found. Forearm muscle activity was higher during a mental reference task with lower exerted force than during the repetitive task. The variation in exerted force was higher during the repetitive task than during a force reference task without mental demands. ' ' CONCLUSIONS ': 'The urinary biomarkers increased during the repetitive task. However, only norepinephrine increased progressively during the 4 hours. Forearm muscle activity during a mental reference task with low exerted force indicated attention-related muscle activity. Finally, it was indicated that repetitive work including high demands for attention is performed at the expense of the precision of the exerted force.
Keywords: electromyography; epinephrine; hydrocortisone; low-level physical demand; low-level repetitive work; mental demand; norepinephrine; physiological response